O poema de Parmênides: Uma leitura não-predicativa do argumento - Pinheiro, Antonio Carlos da Silva (2024)
Parmenides' poem is probably one of the most important texts in the history of philosophy. The influence of the Eleatic can be verified by the writings of the pre- Socratics who followed him and philosophers such as Plato, Aristotle and modern ones such as Heidegger. However, modern interpreters disagree about the reasons that justify this influence. The overwhelming number of academics attribute to Parmenides the epithet of “philosopher of Being”. This denomination seems to result from the ontological reading of the argument presented in B2. Justified by an apparent exhaustion of research on Parmenides, the present investigation sought, as its main objective, to find an alternative interpretation for the argument. Through explanatory bibliographical research, fragments B2, B6, B7 and B8 were mainly analyzed in light of the main modern readings (existential, veritative, predicative and modal) of the verb eínai. It is in an attempt to break with the philosopher's common view of Being”, reinvigorate research on Parmenides, enable new discussions around the points defended and enable the emergence of other perspectives that this investigation sought its justification. We suggest that Non-Predicative Reading, since it meets the necessary conditions required in this research, is relevant to the objectives it pursues.